Learning technology for education in cloud : the changing face of education : 5th International Workshop, LTEC 2016, Hagen, Germany, July 25-28, 2016, Proceedings /: the changing face of education : 5th International Workshop, LTEC 2016, Hagen, Germany, July 25-28, 2016, Proceedings. (2016) - Unknown
No abstract available